2016
DOI: 10.1016/j.ypmed.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette curiosity among U.S. middle and high school students: Findings from the 2014 national youth tobacco survey

Abstract: Curiosity is a potential risk factor for electronic cigarette (e-cigarette) use, which has increased considerably among US youth in recent years. We examined the relationship between curiosity about e-cigarettes and perceived harm, comparative addictiveness, and e-cigarette advertisement exposure. Data came from the 2014 National Youth Tobacco Survey, a nationally representative survey of U.S. middle and high school students. In 2014, 2.5% of middle school and 9.2% of high school students currently used cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…While we expected Hispanic adolescents would have a higher prevalence of susceptibility to each product than non-Hispanic adolescents, this was observed only for e-cigarettes and cigarettes, with curiosity about these products endorsed more often among Hispanic adolescents. This is consistent with previous research ( Margolis et al, 2016 ), and notable, as curiosity predicts future experimentation with smoking independent of susceptibility ( Pierce et al, 2005 ), warranting further examination of factors leading Hispanic adolescents to be more curious about these products. Despite a higher reported prevalence of susceptibility to e-cigarettes and cigarettes among Hispanic adolescents, no significant interactions were observed between ethnicity and susceptibility in predicting future use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While we expected Hispanic adolescents would have a higher prevalence of susceptibility to each product than non-Hispanic adolescents, this was observed only for e-cigarettes and cigarettes, with curiosity about these products endorsed more often among Hispanic adolescents. This is consistent with previous research ( Margolis et al, 2016 ), and notable, as curiosity predicts future experimentation with smoking independent of susceptibility ( Pierce et al, 2005 ), warranting further examination of factors leading Hispanic adolescents to be more curious about these products. Despite a higher reported prevalence of susceptibility to e-cigarettes and cigarettes among Hispanic adolescents, no significant interactions were observed between ethnicity and susceptibility in predicting future use.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, no studies have assessed whether the susceptibility construct ( Pierce et al, 2005 ) functions equally across ethnic groups. Hispanic adolescents who have never smoked report greater intentions to smoke cigarettes in the future compared to white peers ( Bunnell et al, 2015 ) and greater curiosity about e-cigarettes ( Margolis, Nguyen, Slavit, & King, 2016 ). In addition, Hispanic adolescents are more susceptible to cigarettes ( Fulmer et al, 2015 ; Gritz et al, 2003 ), e-cigarettes ( Singh et al, 2016 ; U.S. Department of Health and Human Services, 2016 ), and hookah ( Trinidad et al, 2017 ), compared to non-Hispanic white adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the current study on the association of expectations of costs and benefits with adolescent e-cigarette use are consistent with previous research pertaining to conventional cigarettes and other tobacco products (e.g.. Ashare et al, 2007;Krosnick et al, 2006;Peters, Meshack, Lin, Hill, & Abughosh, 2013). Existing studies suggest that adolescents perceive e-cigarettes as less addictive and lower in health risk relative to conventional cigarettes and that these perceptions are given as a reason to initiate e-cigarette use (Margolis et al, 2016;Pepper, Ribisl, Emery, & Brewer, 2014). In the same vein, Roditis and colleagues (2015) found that adolescents were able to accurately describe negative consequences of conventional cigarette use, but were not able to accurately describe consequences of e-cigarette or marijuana use.…”
Section: Mediationsupporting
confidence: 88%
“…These results are proportional to other studies on e-cigarette use in adolescent (e.g., Doran & Brikmanis, 2016). Further, a recent study found that 25% of U.S. high school students who had never used e-cigarettes reported curiosity about these products, and high levels of curiosity were associated with lower perceptions of harm (Margolis, Nguyen, Slavit, & King, 2016). Therefore, it is imperative to determine potential factors related to adolescent use of e-cigarettes to better inform public policy efforts to curtail ecigarette popularity among this population.…”
Section: Discussionsupporting
confidence: 63%
“…Research examining the relationship between curiosity about e‐cigarette use and intentions to use e‐cigarettes among never users and never smokers is therefore warranted. Given previous research conducted with adolescents suggests that individual factors such as perceptions of e‐cigarette harm are associated with curiosity about e‐cigarette use, it is also important to assess curiosity as a mediator between individual and social variables and use intentions .…”
Section: Introductionmentioning
confidence: 99%